A mixed methods study of seasonal influenza vaccine hesitancy in adults with chronic respiratory conditions. Issue 5 (27th March 2021) - Williams, Lynn; Deakin, Karen; Gallant, Allyson; Rasmussen, Susan; Young, David; Cogan, Nicola
Abstract: Background: Seasonal influenza vaccination is recommended for patients with chronic respiratory conditions, but uptake is suboptimal. We undertook a comprehensive mixed methods study in order to examine the barriers and enablers to influenza vaccination in patients with chronic respiratory conditions. Methods: Mixed methods including a survey (n = 429) which assessed sociodemographics and the psychological factors associated with vaccine uptake (ie confidence, complacency, constraints, calculation and collective responsibility) with binary logistic regression analysis. We also undertook focus groups and interviews (n = 59) to further explore barriers and enablers to uptake using thematic analysis. Results: The survey analysis identified that older participants were more likely to accept the vaccine, as were those with higher perceptions of collective responsibility around vaccination, lower levels of complacency and lower levels of constraints. Thematic analysis showed that concerns over vaccine side effects, lack of tailored information and knowledge, and a lack of trust and rapport with healthcare professionals were key barriers. In contrast, the importance of feeling protected, acceptance of being part of an at‐risk group and feeling a reduced sense of vulnerability after vaccination were seen as key enablers. Conclusions: Our findings showed that the decision to accept a vaccine against influenza is influenced by multiple sociodemographic and psychological factors. Future interventions should provide clear and transparent information about side effects and be tailored to patients with chronic respiratory conditions. Interactions between patients and their healthcare providers have a particularly important role to play in helping patients address their concerns and feel confident in vaccination.